The Preimaginal Phases and Development of Pachycrepoideus vindemmiae (Hymenoptera, Pteromalidae) on Mediterranean Fruit Fly, Ceratitis capitata (Diptera, Tephritidae) - Tormos, José; Beitia, Francisco J.; Böckmann, Elias A.; Asís, Josep D.; Fernandez, Severiano (2017)
The development and morphology of the immature phases of Pachycrepoideus vindemmiae (Rondani, 1875) (Hymenoptera, Pteromalidae) are described from a laboratory rearing culture maintained on Ceratitis capitata (Wiedemann, 1824) (Diptera, Tephritidae) using microscopic techniques, including light and scanning electron microscopy. The surface of the chorion of the egg is granulated, and the micropyle occurs at the anterior end. The labrum of the first instar larva does not have sensilla, and the second to fourth instar larvae have setae on the head. The mature larva is characterized by the position and number of the integumental differentations (sensilla and setae). On completion of larval development, an adecticous and exarate pupa is produced. As for the adult, the mandibles of the pupae are toothed. Five larval instars are recorded, based on statistical analyses of the sizes of the larval mandibles in combination with characters such as the number of exuviae and excretion of the meconium. Developmental time from egg to adult emergence was similar to 18-20 days for males and similar to 21-23 days for females at 21-26 degrees C, 55-85 relative humidity, and a 16L:8D photoperiod. The results show that the eggs and different larval instars of this parasitoid can be unambiguously identified only by scanning electron microscope.